Survei Minat Member Terhadap Olahraga Pound Fit Di Atlas Sports Club Surabaya - Muhammad Dicy Yanuar; Soni Sulistyarto (Pusat Riset dan Inovasi Nasional, 2024)
Everyone has an interest in satisfying the needs of life. But these desires are not necessarily expressed implicitly for adults. A strong need that is always expressed in tangible form has a significant impact on the defense of these interests. So is interest in the world of sports, one of which is interest in pound fit sports which is hot and widely known by the public, especially the younger generation. The main reason for the high interest in pound fit sports is its pleasant movements. Moreover, the amount of pound fit content uploaded on social media is an attraction for the younger generation to express their interest in pound fit sports. Many sports venues also present pound fit, one of which is Atlas Sports Club Surabaya. Pound fit exercise carried out on the page of Atlas Sports club Surabaya in addition to providing health benefits can also increase the social sense and familiarity of the members who have joined. This study aims to determine members' interest in pound fit sports at Atlas Sports Club Surabaya. The research method in this study used quantitative descriptive and survey methods which were carried out directly by distributing questionnaires to 20 respondents. The results of this study show that members' interest in pound fit sports at Atlas Sports Club Surabaya is included in the high category. This is evidenced by the results of calculations and data analysis of 92% of the interest of Atlas Sports Club Surabaya members intrinsically and 91% of the interest of Atlas Sports Club Surabaya members extrinsically.